Textbook of environmental chemistry - Pani, Balram (I.K. International Publishing House, 2009)
Provides fundamental knowledge of the principles related to the environment and its chemistry so as to meet the requirements of students and teachers. The book explores biological resources and their relationship with physical and chemical aspects of the environment. Emphasis is given to regional as well as global environmental problems.